031 The effectiveness of online ACL injury prevention education for sports coaches. (3rd March 2020) - Janosky, Joseph; Ologhobo, Titilayo; Rusomano, James; Goldsmith, Sandra; Robbins, Laura
Abstract : Background: Onsite educational interventions for sport coaches demonstrate effectiveness in improving the knowledge needed to effectively employ neuromuscular training (NMT) programs but are resource-intensive and reach relatively small numbers of coaches. Online educational interventions can deliver information efficiently to large numbers of individuals but have not yet demonstrated effectiveness that is equivalent to live education interventions. Objective: The purpose of this study is to evaluate the effectiveness of online ACL injury prevention education for sports coaches. Design: Longitudinal survey. Setting: This study was conducted with secondary school sports coaches. Patients (or Participants): 3, 000+ coaches from throughout the world completed an online education program. Matched pre/post-intervention survey data was collected from 1, 641 participants. Interventions (or assessment of risk factors): An online workshop was used to train sports coaches to effectively incorporate NMT programs into their daily training regimens. A series of instructional videos delivered content through an online learning management system. Main outcome measurements: Outcome measures included behavior change metrics including knowledge and self-management. Results: Overall mean knowledge scores increased by 28.5% (p ≤ 0.001) with 54.9% of all participants demonstrating an increase in knowledge immediately post-intervention. One month after program completion, 50.9% of respondents reported implementing a Neurodynamic warm-up with their team while 63.2% of these respondents reported that they always implemented a Neurodynamic warm-up with their team before practices/games. Three months after program completion, 88.9% of respondents reported that they had implemented a Neurodynamic warm-up with their team, while 72.2% of these respondents reported that they always implemented a Neurodynamic warm-up with their team before practices/games. Conclusions: Online ACL injury prevention education is successful in improving the knowledge and self-management of a diverse group of sports coaches. These findings support including online education interventions in comprehensive ACL injury prevention programs to support program adoption and long-term behavior change.